2018
DOI: 10.1002/jcla.22390
|View full text |Cite
|
Sign up to set email alerts
|

Ascorbic acid—A black hole of urine chemistry screening

Abstract: Obtained results indicate that it is necessary to determine diagnostic accuracy of used dipstick in order to define purpose of urinalysis. It is very important to choose dipstick with ascorbic acid indicator and to examine ascorbic acid impact on dipstick analytes independently of manufacturer claims.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 13 publications
1
13
0
Order By: Relevance
“…Ascorbic acid begins to interfere with hemoglobin at low concentrations (0.03 mg/ dL), so it can easily cause false-negative results in occult blood test. Adriana Unic et al [3] showed similar results in their study. The immunological method based on antigenantibody reaction is more specific and free from the interference of ascorbic acid.…”
Section: Discussionsupporting
confidence: 76%
“…Ascorbic acid begins to interfere with hemoglobin at low concentrations (0.03 mg/ dL), so it can easily cause false-negative results in occult blood test. Adriana Unic et al [3] showed similar results in their study. The immunological method based on antigenantibody reaction is more specific and free from the interference of ascorbic acid.…”
Section: Discussionsupporting
confidence: 76%
“…AA causes falsely negative results for glucose, blood, nitrite and bilirubin using iChem Velocity urine test strips. 9 With the exception of glucose, other parameters are affected at the lowest positive results for AA (20–40 mg/dL or 1+), while glucose is less sensitive to AA interference (> 40 mg/dL or 2+). Based on these results, four possible errors were identified due to AA interference: falsely negative glucose (U-Glc), blood (U-Hb), nitrite (U-Nit) and bilirubin (U-Bil).…”
Section: Methodsmentioning
confidence: 92%
“…Urinary glucose determined by urine test strip correlates well with values measured using reference method. 9 Bilirubin in urine can be a useful indicator of hepatic damage, especially when battery of hepatic tests is not initially ordered. Several limitations of measurement of bilirubin in urine are already known.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations